Genetic comparison of different human population groups using internal transcribed spacer sequence - G. Alatiyah, Muna I. Hadi (2013)
Genetic identity testing for humans has been used to examine the variations in the polymorphic regions of the human DNA. These methods include the RFLP (Restriction fragment length polymorphisms), the STR (short tandem repeats) markers that are most commonly used loci for human identification as well as the mtDNA or Y chromosome in forensic medicine and paternity tests. Currently, the internal transcribed spacer (ITS) region is used for the evolutionary analysis of different species of animals, plants, fungi, yeast. However, the ITS region is yet to be used in genetic identity testing for humans. In this study, the genetic comparison of different human population groups using ITS sequence of mtDNA was performed. Two segments of the region of human mtDNA were selected and sequenced in order to determine if any sufficient single nucleotide polymorphisms (SNPs) exist and if it is suitable for genetic identity testing in human. Specific primers were designed to amplify the ITS regions using PCR from sample extracted from the blood samples of different nationalities of students from Faculty of Biosciences and Bioengineering, UTM (Iran, Nigeria, Kurdistan, Malaysia, Palestine and Luxembourg). The result from the bioinformatics analysis showed a significant number of SNPs in the ITS region. There are 40 SNPs found in the ITS sequences and 35 SNPs in the NADH1sequences of the mtDNA. The phylogenic analysis of the result revealed the phylogenetic relationship and a distinct genetic difference between the different nationalities that may be used as a marker for human genetic identification in the future.